Healthcare professionals' stigmatization of men with anabolic androgenic steroid use and eating disorders. (September 2015) - Yu, Jessica; Hildebrandt, Thomas; Lanzieri, Nicholas
Highlights: We present healthcare providers with four clinical vignettes. We examine providers' attitudes toward men presenting with different clinical problems. Providers' exhibited negative attitudes toward the male eating disorder patient and steroid user. Results may help explain steroid users' documented distrust of healthcare professionals. Abstract: Building upon previous research on the stigmatization of individuals with eating disorders (EDs), the present study sought to evaluate healthcare providers' attitudes toward male anabolic androgenic steroid (AAS) users. Healthcare providers ( N  = 148) were first randomly assigned to read one of four vignettes describing a male AAS user, ED patient, cocaine user, or healthy control. Each provider then rated, on a scale of −3 to +3, how strongly either word in one of 22 word-pairs described his or her feelings toward the person described in the vignette. Results indicated that providers perceived the ED and AAS use patients less favorably than the cocaine user or healthy adult, suggesting that the two groups may be stigmatized by health providers. Given the psychiatric and medical risks associated with AAS use and EDs, reducing bias may help reduce the personal suffering and public health burden related to these behaviors.